Riding the Wave: Monetary Responses to Aid Surges in Low-Income Countries. - Buffie, E; Adam, C; Connell, S; Pattillo, C (Elsevier, 2008)
We focus on the management of highly persistent shocks to aid flows in the presence of currency substitution by the domestic private sector. Such shocks have beneficent long-run effects, but when currency substitution is high they can produce dramatic macroeconomic management problems in the short run. What is the appropriate mix of money and exchange rate targeting in such cases, and the role of temporary sterilization? We analyze these and related issues in an intertemporal optimizing model that allows a portion of aid to be devoted to reducing the government's seigniorage requirement. Our results show that a managed float, with little or no sterilization of increases in the monetary base, supports the smooth absorption of the increased aid without incurring higher inflation, higher real interest rates or overshooting of the real exchange rate.